(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The research aims to identify how to audit potential liabilities and contingent liabilities in light of the pandemic and its reflection on the auditor’s report. The research problem is represented by the complexity of the process of checking potential liabilities and contingent liabilities in insurance companies, which was negatively reflected in the auditor’s neutral technical opinion. The researchers hypothesize that auditing potential liabilities and contingent liabilities in light of the Corona pandemic is positively reflected in the auditor’s report. The research concludes that the process of checking potential liabilities and contingent liabilities is complicated in insurance companies operating in environments suffering from the Corona pandemic and similar situations, which was negatively reflected in the auditor’s neutral technical opinion. The researchers recommend that it is necessary to hold training courses for employees of insurance companies and for workers in auditing companies and offices to familiarize them with international accounting standards in general and Financial Reporting Standard (17) for the insurance industry to develop applications for auditing potential liabilities and contingent liabilities for insurance activities. The insurance company’s commitment to the actuary’s recommendations leads to support the company’s financial capacity in the long term, and that the authority supervising the insurance sector is responsible for defining the procedures for appointing the actuary, his duties and responsibilities, which constitute an important element in measuring and analyzing future risks, pricing services, defining terms of reference and reserves, and achieving Balance between assets and liabilities.